Growth of Nile tilapia post-larvae from broodstock fed diet with different levels of digestible protein and digestible energy - Sousa, Silia Maria De Negreiros; Freccia, André; Santos, Lilian Dena Dos; Meurer, Fábio; Tessaro, Lucélia [UNESP]; Bombardelli, Robie Allan (Sociedade Brasileira de Zootecnia, 2013)
This study was carried out to evaluate the influence of different levels of digestible energy and digestible protein in diets of Nile tilapia (Oreochromis niloticus) broodstock on offspring growth during sex reversal stage. A total of 2,700 post-larvae (8.2±0.001 mg) derived from breeders fed nine diets with distinct levels of digestible protein (28, 34 and 40% DP) and digestible energy (2,800; 3,400; and 4,000 kcal DE.kg-1) were stored in twenty-seven 70 L tanks. After 30 days of growth, their average final weight (AFW, g), average weight gain (AWG, g), final standard length (SL, cm), condition factor (CF), specific growth rate (SGR, %/day), stock uniformity (UNI, %), survival (SUR, %) and sex reversal rate (SRR, %) were measured. Although female nutrition is thought to influence the performance or quality of progeny during early life stages, no influence of diets supplied to broodstock was detected on any parameter. Nonetheless, the offspring presented commercially satisfactory growth rates. Thus, diets containing 28% of digestible protein and 2,800 kcal of digestible energy.kg of diet-1 can be used to feed Nile tilapia broodstock without jeopardizing offspring performance during the sex reversal phase.
Keywords: fry; nutrition; Oreochromis niloticus; reproduction; sex reversal